The Weaknesses in Handling Fraud in The Capital Market Practices - Suhanan, Aan; Gunarto, Gunarto; Mashdurohatun, Anis (Universitas Islam Sultan Agung, 2023)
The weaknesses of the legal substance relating to the handling of fraud in the Capital Market practices are fundamentally contained in the substance of Law Number 8 of 1995 on Capital Market (